Coherent Solution‐phase Synthesis of a Germanium‐Graphitic Nanocomposite and Its Evaluation for Lithium‐Ion Battery Anodes: Non‐innocent Role of the Mashima Reagent. Issue 5 (14th February 2020) - Akula, Naveenkumar; Sharma, Neha; Lohegaonkar, Apurva; Ogale, Satishchandra B.; Majumdar, Moumita
Abstract: The organosilicon reagent 1, 4‐bis‐(trimethylsilyl)‐1, 4‐diaza‐2, 5‐cyclohexadiene 2 plays the binary role of the simultaneous reduction of GeCl2 .dioxane 1 dissolved in oleylamine to Ge nanocrystals and the formation of graphitic sheets under hot‐injection conditions. This colloidal synthetic route to germanium nanocrystals embedded on N ‐doped graphitic nanosheets Ge/NG is free of any template or catalyst and involves easy purification techniques. The Ge/NG/C obtained after carbonization has been explored for anode performance in lithium‐ion batteries. Both Ge/NG and Ge/NG/C can be obtained on a gram scale and are bottleable under argon for months. Abstract : Graphitic nanosheets were obtained coeval with the Ge nanocrystals under the hot‐injection conditions from a mixture of GeCl2 .dioxane, oleylamine and 1, 4‐bis‐(trimethylsilyl)‐1, 4‐diaza‐2, 5‐cyclohexadiene. This template‐ and catalyst‐free graphitization method is gram scalable and modular for making nanostructures with tuneable compositions. The annealed germanium‐graphitic nanocomposite has been tested as anode material in lithium‐ion batteries.